1997
DOI: 10.1128/jb.179.12.3936-3943.1997
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of a variety of chimeric dioxygenases constructed from two biphenyl dioxygenases that are similar structurally but different functionally

Abstract: The biphenyl dioxygenases (BP Dox) of strains Pseudomonas pseudoalcaligenes KF707 and Pseudomonas cepacia LB400 exhibit a distinct difference in substrate ranges of polychlorinated biphenyls (PCB) despite nearly identical amino acid sequences. The range of congeners oxidized by LB400 BP Dox is much wider than that oxidized by KF707 BP Dox. The PCB degradation abilities of these BP Dox were highly dependent on the recognition of the chlorinated rings and the sites of oxygen activation. The KF707 BP Dox recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 30 publications
4
94
1
Order By: Relevance
“…Differences in CB dioxygenation between BDO-H09 and -H03 clearly demonstrate the importance of region αE, in agreement with findings made in the LB400\KF707 system (Erickson & Mondello, 1993 ;Kimura et al, 1997 ;Mondello et al, 1997). However, the difference in CB dioxygenation between BDO-H09 and BDO-LB400 was not expected on the basis of those studies.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Differences in CB dioxygenation between BDO-H09 and -H03 clearly demonstrate the importance of region αE, in agreement with findings made in the LB400\KF707 system (Erickson & Mondello, 1993 ;Kimura et al, 1997 ;Mondello et al, 1997). However, the difference in CB dioxygenation between BDO-H09 and BDO-LB400 was not expected on the basis of those studies.…”
Section: Discussionsupporting
confidence: 78%
“…As regions αG and αH have been shown to be of minor importance, this result highlights a significant effect of region αF. Previously, Kimura et al (1997) and Mondello et al (1997) identified a major contribution of aa 377 (LB400 numbering) on substrate specificity. This is one of the three amino acid differences between regions αF of the LB400 and P6 subunits.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Previous studies with class II ARHDO systems have demonstrated that the major determinants of the fundamental catalytic properties such as substrate and product spectra reside within the C-terminal part of the large or a-subunit (Erickson & Mondello, 1993;Kimura et al, 1997;Mondello et al, 1997;Beil et al, 1998;Zielinski et al, 2002), although the small or b-subunit has occasionally been reported to exert some influence on these properties (Furukawa et al, 1994;Hurtubise et al, 1998). Recently, it has been shown that the C-terminal 60 aa of the a-subunit are of minor importance for these properties (Zielinski et al,…”
Section: Introductionmentioning
confidence: 99%